Technology readiness in enterprise resource planning gamification to improve student learning outcomes - Budi Septiawan; Ayatulloh Michael Musyaffi; Martin Quinn; Ifa Ratifah (Institute of Advanced Engineering and Science, 2023)
In online learning, students often experience problems related to the use of technology. One of them is enterprise resource planning (ERP) technology. Therefore, this study aimed to analyze the technology readiness index (TRI) to measure the extent to which students’ readiness for ERP gamification. This research targets students who use ERP gamification during management information systems and accounting information systems courses. The technique of determining the sample is using a census. So that all the population is used as a sample of 153 students in Indonesia, then analyzed using TRI. Through TRI analysis using SEM PLS, most students studying ERP gamification have a medium readiness index. The findings of this research showed that students are very close to technology, so they have a strong adoption of technology. Most students have an explorer character where they are enthusiastic and have high curiosity about learning ERP gamification. Pioneers who need a little encouragement from external parties to adopt ERP gamification. However, typical skeptics should be given a concrete example of the benefits of using ERP in learning. This research is also a benchmark for developing technology-based learning media according to the characteristics of students who are intended for technology in higher education.